The Influence of Lesson Plan to the Learning Process at MTs Al-Washliyah Tebing Tinggi - Balqis Fadiah; Lainatusshifa; Putri Maulida; Rifky Amardiaz; Rizki Adha; Siti Ismahani (Yayasan Zia Salsabila, 2023)
This research the aim was to find out how to collect data from several teachers at the MTs Al-Washliyah Tebing Tinggi. Data collection was carried out by giving teachers a questionnaire in the form of questions related to the problem to be studied using quantitative and qualitative methods. From the research results it can be seen that most teachers strongly agree that lesson plans have an important role to support the success of the learning process. Among them there were 4 teachers who strongly agreed and 1 teacher who agreed. There were no teachers who disagreed with the questions we asked. This means that almost 80% of teachers in schools strongly agree and 20% of teachers only agree with this question.